Best of the OPS 1993-94 scientific exhibit winners (USA : American Academy of Ophthalmology, 1996)
Producer) Contains 110 digital images. Features winners from the 1993-1994 annual scientific exhibit of the Ophthalmic Photographers' Society.
'A joint project of the American Academy of Ophthalmology and the Ophthalmic Photographers' Society in association with Digital Galleries, Inc.'--Container.
System requirements: IBM-compatible 486 or better computer; minimum 8 MB RAM; Windows 3.1 or higher; double-speed CD-ROM drive or better; SVGA monitor; 24-bit col. graphics capability; hard disk or other mass storage device.
Keywords: Eye Diseases; Eye